Outcome of enzyme replacement therapy for hematological and visceral manifestations in children with acid sphingomyelinase deficiency: a single center experience in upper Egypt - Mervat A. M. Youssef; Esraa Hefzy Shaker; Nahed A M Saleh (Molecular and Cellular Pediatrics)
Abstract Background Thrombocytopenia is the most common hematologic manifestation of acid sphingomyelinase deficiency (ASMD). The introduction of enzyme replacement therapy (ERT) represents significant progress in the treatment landscape of this disorder. This study presents the largest pediatric case series of ASMD to date, providing valuable insights into the real-world application of ERT in affected children. Methods Ten children with ASMD (five with type B and five with type A/B) received ERT for one year. Growth parameters, complete blood counts, abdominal ultrasonography, liver function tests, lipid profiles, and neurological assessments were conducted at baseline and subsequently every three months. In addition, chest high-resolution computed tomography (HRCT) and dual-energy X-ray absorptiometry (DXA) were performed at baseline and repeated after one year. Results No serious infusion-related reactions (IAR) were recorded. However, one patient developed a mild urticarial rash, while another experienced pyrexia. Anemia was present in all children at baseline. A significant increase in hemoglobin levels starting at week 12 (p = 0.02) with peak levels observed at week 50. Thrombocytopenia was present in 60% of patients at baseline. Platelet counts did not show a significant change at week 12 (p = 0.3), but a significant increase was observed after 24 weeks (p = 0.0196), and counts peaked at week 50 (p = 0.0057). There was a significant reduction in liver and spleen sizes, as well as lipid profile parameters. In addition, gradual improvements were observed in interstitial lung disease scores and bone mineral densities throughout the study course. Conclusion Our findings indicate that olipudase alfa provides significant benefits in key hematological and visceral clinical outcomes in pediatric patients with ASMD.